Edukasi Kesehatan Kulit pada Remaja di Sekolah Kalam Kudus II Jakarta - Sukmawati Tansil Tan; Alexander Halim Santoso; Giovanno Sebastian Yogie; Dean Ascha Wijaya; Fernando Nathaniel; Anggita Tamaro (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Skin diseases are a common problem among people, especially teenagers. Hormones, lifestyle and personal hygiene play a role in the occurrence of various skin problems in teenagers. If not treated, it can cause various disorders, especially quality of life. This health education was carried out to all class X students of SMA Kalam Kudus II Jakarta using the counseling/seminar method. In addition to enhancing knowledge, this education may provide awareness to teenagers to pay attention to their skin health so that various skin diseases can be avoided. Furthermore, it is hoped that this can become a basis for society to maintain healthy skin, so that the incidence of skin diseases in the community can be reduced.